Electronic structure and effectively unpaired electron density topology in closo -Boranes: Nonclassical three-center two-electron bonding - Lobayan, Rosana Maria (2011)
This article provides a detailed study of the structure and bonding in closo-borane cluster compounds X2B3H3 (X = BH-, P, SiH, CH, N), with particular emphasis on the description of the electron distribution using the topology of the quantum many-body effectively unpaired density. The close relationship observed between the critical points of this quantity and the localization of the electron cloud allows us to characterize the nonclassical bonding patterns of these systems. The obtained results confirm the suitability of the local rule to detect three-center two-electron bonds, which was conjectured in our previous study on boron hydrides. © 2011 American Chemical Society.